Forced degradation of gliquidone and development of validated stability-indicating HPLC and TLC methods - Mohamed Refaat El-ghobashy; Ali Mohamed Yehia; Aya Helmy Helmy; Nadia Fayek Youssef (Universidade de São Paulo, 2018)
Forced degradation studies of gliquidone were conducted under different stress conditions. Three degradates were observed upon using HPLC and TLC and elucidated by LC-MS and IR. HPLC method was performed on C18 column using methanol-water (85:15 v/v) pH 3.5 as a mobile phase with isocratic mode at 1 mL.min-1 and detection at 225 nm. HPLC analysis was applied in range of 0.5-20 µg.mL-1 (r =1) with limit of detection (LOD) 0.177 µg.mL-1. TLC method was based on the separation of gliquidone from degradation products on silica gel TLC F254 plates using chloroform-cyclohexane-glacial acetic acid (6:3:1v/v) as a developing system with relative retardation 1.15±0.01. Densitometric measurements were achieved in range of 2 -20 µg /band at 254 nm (r = 0.9999) with LOD of 0.26 µg /band. Least squares regression analysis was applied to provide mathematical estimates of the degree of linearity. The analysis revealed a linear calibration for HPLC where a binomial relationship for TLC. Stability testing and methods validation have been evaluated according to International Conference on Harmonization guidelines. Moreover, the proposed methods were applied for the analysis of tablets and the results obtained were statistically compared with those of pharmacopeial method revealing no significant difference about accuracy and precision.